PENGETAHUAN SISWA SMK NEGERI 1 PERCUT SEI TUAN TENTANG PENCEGAHAN PENYEBARAN COVID-19 DENGAN METODE 5 M - Devi Novita Damanik; Mona Hastuti (Jurnal Maternitas Kebidanan, 2021)
In dealing with the Covid-19 pandemic, it is necessary to have the participation of the community in synergy with the government, so that it can break the chain of the spread of Covid-19. The country's success in dealing with the Covid-19 outbreak cannot be separated from the community's compliance with the rules and policies made by the government, one of which is by applying the 5M method as an effort to prevent the spread of COVID-19. This  research  was  aimed To know the level of knowledge of SMKN 1 PST students about preventing the spread of the Corona Virus with 5M. This research is a quantitative study using a quantitative descriptive research design using univariate data analysis. Univariate analysis to describe descriptively the frequency distribution of respondents' demographic data consisting of: gender, age, class. The knowledge level variable will describe the amount and level of knowledge with a level presentation. The results showed that the average age of the respondents was at the age of 17 years, namely 52 people (53.11%). The gender of the majority of the respondents was 50 men (52.08%). And each response is in the same class average between class X, XI and XII, namely 34.33%, 33.33% and 32.39%. Presentation of knowledge level: good knowledge 40 people (41.67%), sufficient knowledge 36 people (37.50%) and less knowledge 20 people (20.83%). The results of this study indicate that there are students who have less knowledge as much as 20.83%.